Proceedings of the Proceedings of the 1st Conference of Visual Art, Design, and Social Humanities by Faculty of Art and Design, 2020
DOI: 10.4108/eai.2-11-2019.2294888
|View full text |Cite
|
Sign up to set email alerts
|

Civic Education: Fostering Global Citizenship among Indonesian Students

Abstract: This study aims to analyze the curriculum content of Civic Education in Indonesia and its ability to prepare students for global citizenship. Global issues such as global economy, international conflicts, interdependency, climate changes, and natural resource conflicts, create yet other issues which can be resolved at best with a satisfactory education system. Civic Education as a multidimensional education aims to foster global citizenship among Indonesian students through the topics included in the curriculu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Material aspects regarding legal protection, aspects of cultural diversity, human rights, are the material discussed in the school curriculum. Meanwhile, the value aspects included in the curriculum include; mutual respect, tolerance, empathy, respect for diversity of ethnicity, religion, race, language [25].…”
Section: Design Of Global Citizenship Education Into the School Curri...mentioning
confidence: 99%
“…Material aspects regarding legal protection, aspects of cultural diversity, human rights, are the material discussed in the school curriculum. Meanwhile, the value aspects included in the curriculum include; mutual respect, tolerance, empathy, respect for diversity of ethnicity, religion, race, language [25].…”
Section: Design Of Global Citizenship Education Into the School Curri...mentioning
confidence: 99%
“…The previous research conducted by Luthfi, Muchtar, Bestari, Waldi, & Prasetiyo (2020) revealed that the national curriculum had included global competencies in the aspect of knowledge of citizenship, covering legal protection, diversity, and human rights as the topics. On the other hand, citizenship skills are studied in each topic, including empathy, namely the principle of mutual respect and respect for diversity in ethnicity, religion, race, culture, and gender.…”
Section: Introductionmentioning
confidence: 99%
“…Untuk memberikan pengetahuan tentang kesadaran global, diperlukan pengetahuan baru dari para pengajar atau guru. Pada sekolah Indonesia dan Thailand, keragaman merupakan ciri khas yang mencerminkan masyarakat multikultural dan multietnis di mana sekolah-sekolah tersebut berada (Kennedy & Brunold, 2015;Luthfi et al, 2020;Sutrisno et al, 2023;Tan & Vickers, 2024). Para siswa berasal dari berbagai latar belakang, agama, dan budaya, sehingga menciptakan suatu pengalaman dan perspektif yang beragam di dalam komunitas sekolah.…”
unclassified